Seasonal evolution of the zooplankton community in two riverine wetlands of the Ticino River (Lombardy, Northern Italy). Issue 3 (21st August 2014) - Paganelli, Daniele; Saltarelli, Marta; Sconfietti, Renato
<x content-type="archive" xml:space="preserve">Abstract</x> Riverine wetlands are vulnerable ecotonal environments and are often threatened by human activities. A project supported by the Cariplo Foundation, called "Ecological and hydromorphological requalification of wetlands in the Ticino area around Pavia" (South-East Lombardy, Northern Italy), was started in 2010 with the aim of improving the chemical, bio-ecological and hydrological conditions of these wetlands. In line with the aim of this project, we selected two wetlands near the main course of the Ticino River for investigation, one of which is impacted by a combined sewer overflow from the sewerage networks which is always active (San Lanfranco (SL) wetland), whereas the other (Topo (TO) oxbow lake) is less directly impacted by anthropogenic activities. In this paper, we report the ecological situation of these two wetlands before the requalification process by investigating the way the zooplankton assemblages, considered as bio-indicators, respond to anthropogenic pressure. Overall, we collected 19 taxa: 4 cladocerans, 1 copepod and 14 rotifers. In the TO oxbow lake, we found a stable community, dominated by the cladoceran Bosmina longirostris. By comparison, in the SL wetland we found a pioneer community, dominated by the juvenile stage of the copepod Thermocyclops dybowskii. The SL wetland was shown to be most urgently in need of improvement and is therefore first in line for requalification, whereas the TO oxbow lake needs less drastic measures to ensure the long-term ecological functioning of the aquatic environment. After these requalification activities, a systematic zooplankton survey will be carried out to monitor the evolution of the riverine wetlands.